Suicide After Evaluation for Involuntary Psychiatric Commitment—Who Gets Them and What Influences Survival Time?. Issue 5 (21st March 2016) - Vannoy, Steven D.; Andrews, Bonnie K.; Srebnik, Debra
Abstract : Although involuntary psychiatric hospitalizations are associated with suicide risk, little is known about the relationship between evaluation for involuntary detention and suicide. We analyzed data on 10, 082 suicides from 2000 to 2011 to examine demographics related to evaluation for detention and the association between demographics and evaluation dispositions on survival time. Evaluation preceded 11% of suicides; 53.8% of deaths occurred within 365 days, 6.5 times the expected rate. Males and older individuals were least likely to have been evaluated. Minority status and referral disposition influence 30‐day survival time. Risk is highly concentrated in the first year following evaluation.